Barriers and Enablers to Vocational IT Education: Responding to South Africa's ICT Skills Crisis - Ryklief, Yusuf (Department of Information Systems, 2019)
Advancement in digital technologies has directed the attention of developing countries toward ICT’s to aid socio-economic advancement. These technological solutions cannot be implemented as an island, and its effective use requires proportionate advancement in local ICT skills levels to ensure effective operation and sustainability. Increasingly demands for skilled ICT workforce globally is placing pressure on institutions to be more responsive, and to produce ICT graduates with a skillset that is more relevant and closer aligned to the needs of industries. In South Africa the ICT skills landscape remains an object of conflicting reports. Depending on who the question is posed to, the paradoxical views describe the country as either facing a critical shortfall of skilled ICT professionals, or that droves of qualified ICT professionals cannot find suitable employment. These contradictory notions suggest a possible mismatch between the current skills of ICT professionals, the supply of appropriately skilled ICT graduates by education institutions and industry demands for appropriately skilled ICT workforce. Attempts to reform the country’s skills landscape has resulted in numerous policy pronouncements and skills development strategies by the public and private sectors with limited success. This focus of this study was to evaluate the National Certificate Vocational Information Technology (NCV IT) strategy, an ICT skills development mandate issued to South African Technical and Vocational Education and Training (TVET) Colleges in response to the country’s ICT skills shortage. Using the Design-Reality Gap Model, the study evaluated the intended design objectives and current reality of NCV IT to gauge its status ten years post inception. While the South African government boasts increasing access to the programme, little focus is given to the handful of graduates who successfully complete the programme and even less who find meaningful employment. The study further operationalised the Design Reality Gap Model to demonstrate its applicability and value in the evaluation of Vocational Education and Training (VET) programmes. Primary data informing the study was from focus group discussions and semi-structured interviews with key NCV IT stakeholders. Secondary data supporting the study was collected by reviewing key documents relating to NCV IT. The findings reveal significant gaps exist between the programme’s intended design and current reality, indicative of the key challenges hindering the effective delivery of its ICT skills promise. It further positions the NCV IT programme as a post-apartheid dumping ground for financially disadvantaged and academically underperforming individuals hoping to achieve self-sufficiency. What was envisaged to be an enabler for the country’s ICT skills development has instead become a black hole for public funding yielding no return on investment. Recommendations were suggested along particular structural dimensions to improve the NCV IT programme, and the development of a more effective vocational ICT skills development strategy.